“too poetic” (Arist. Rh. 1406b10): about the music of the arguments in Gorgias’ Defense of Palamedes (El Hilo de la Fabula, 2022)
The musicality of the poetic style of the Gorgian prose has been a feature discussed in its own language and even not always translated in modern languages’ versions of the text. In this article we seek to: 1. explore some of the criticisms of Gorgias based on passages from Aristotle's Rhetoric; 2. show the coincidence of the common places ('topoi') in Gorgias and Aristotle used for the specific arguments of the judicial genre; 3. interpret the musicality of poetic figures in the construction of arguments and consider their persuasive power. Finally, we will present our criteria for the translation of the musicality of Gorgias's poetic style in the piece In defense of Palamedes (2021).
Keywords: Gorgias; Palamedes; rhetoric; poetic style; musicality